OCCURRENCE OF ECTOPARASITES ON A PEAFOWL (PAVO CRISTATUS, LINN.) IN TAMIL NADU - N. Jeyathilakan; D. Basheer Ahamad; B. Dhivya; J. Selvaraj (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present communication deals with concurrent infestation of lice and tick in a peafowl from Cauvery delta region of Tamil Nadu. External examination of the bird revealed presence of six lice and seven tick specimens. The ectoprasites were processed and examined under microscope. The lice and tick specimens were identified as Goniodes pavonis and nymphal stages of Haemaphysalis sp respectively. This is the first study to establish the concurrent infection of Goniodes pavonis and Haemaphysalis sp in peafowl from Cauvery delta region of Tamil Nadu and also first report of Goniodes pavonis in peafowl from India.